Potential of cumin essential oil as inhibitor of deamination during ensiling process: A meta-analysis and in-silico approach - Susanto Irwan; Mahendra Fachrur R.; Rahmadani Mardiah; Ridwan Roni; Jayanegara Anuraga (BIO Web of Conferences)
Silage produced from high-protein forage is susceptible to amino acid deamination, resulting in ammonia production. One strategy in the development of novel additives is to employ the in-silico method and meta-analysis. Cumin essential oils (EOs) contain metabolite chemicals that may serve as deamination inhibitors, necessary for further research both in vitro and in vivo. This study intends to conduct virtual screening through molecular docking simulations of compounds derived from cumin essential oil as deamination inhibitors in silico, alongside a meta-analysis to validate their efficacy on fermentative products during ensiling. This work examines the relationship between the ligand of Cumin EOs and the particular glutamate dehydrogenase (GDH) receptor specific from Clostridium sp., a common contaminant in silage. The observed metrics included energy values derived from the Vina program, pharmacokinetic analysis, and free ammonia concentration in silage. The meta-analysis results indicated that cumin essential oil supplementation effectively decreased free ammonia during ensiling (P < 0.05). However, computer simulations showed that the α-hederin molecule compound was the most effective ligand tested as a deamination inhibitor. In conclusion, it is proposed that Eos cumin might act as a deamination inhibitor in silage while it is being stored.